Pandemic Corona virus (Covid-19): Twitter Analysis as a Social Media Information Platform in Indonesia - Herdin Arie Saputra; Anang Setiawan; Dafrin Muksin (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2021)
Social media Twitter as a means of providing information at this time, during the Covid-19 pandemic, the Government's announcement, in this case, the Twitter account from the Ministry of Health of the Republic of Indonesia, will become a public reference. This study uses the Nvivo12 Plus technology application to obtain data. This study reveals the use of social media Twitter about spreading social media information on Twitter with (hashtag) # COVID19, # Covid19Indonesia, and Twitter accounts from the Ministry of Health of the Republic of Indonesia. Qualitative methods are used to find a social media model that is used as a mass communication channel. The data results show that many intense social media campaigns discuss all the impacts of the Coronavirus (Covid-19) and discussions about selling masks and hand sanitizer at relatively high prices. The Ministry of Health's Twitter account provides information related to prevention and motivates the public always to implement social distancing, physical distancing, large-scale social distancing (PSBB), stay at home, don't return home, stay clean, and always wash their hands with soap and hand sanitizer, and use the face mask